Translation and Cultural Adaptation of the Long Coronavirus Disease (Covid) Symptom and Impact Tools for the Chilean Population; [Traducción y Adaptación Cultural de Los "Long Coronavirus Disease (Covid) Symptom and Impact Tools" Para Población Chilena] - Bachelet-Norelli, V; Silva-Ayarza, I; Gomolan-Gonzalez, P (Medwave Estudios Ltda, 2024)
INTRODUCTION The Long Coronavirus Disease (COVID) Symptom and Impact Tools (ST and IT) were published in English in 2022 to monitor the symptoms and impact of persistent COVID-19. ST includes 53 symptoms selected by the patient. IT includes six aspects of life that the patient must rate from 1 to 10 points. We aim to report the results of the cultural adaptation of both instruments for the Chilean population, together with the content validity of the adapted instrument. METHODS The cultural adaptation was carried out in five steps: 1) translation from English to Spanish, 2) synthesis, 3) back-translation, 4) review by the editorial board, and 5) testing the questionnaire with ten patients; they answered both questionnaires and seven questions assessing their understanding of the TI and their opinion on whether the instrument reflected the impact of prolonged COVID-19 on their lives. The content validity of the final version of the IT was assessed by 14 experts. RESULTS The main outcome is the two final questionnaires adapted for use in Chile. Most patients responded with the best concept or approval for all items. Content validity showed acceptable results, with an average content validity index of 0.9 and Aiken s V for the relevance of the questionnaire in general of 0.83 (95% CI 0.69 to 0.92). For one item, Aiken s V was less than 0.7 (95% CI 0.5 to 0.8). CONCLUSIONS This study provides Chilean health authorities and health providers with an instrument for assessing the impact of prolonged COVID-19 on core aspects of people s lives. © 2024, Medwave Estudios Ltda. All rights reserved.